Effects of high-intensity interval training on aerobic and anaerobic capacity in olympic combat sports: a systematic review and meta-analysis - Yue, Fengshan; Wang, Yuyan; Yang, He; Zhang, Xiaolei (Frontiers in Physiology, 2025)
This study aimed to summarize the findings of research comparing the effects of high-intensity interval training (HIIT) with active controls (alternative training methods) and passive controls (no exercise intervention) on aerobic and anaerobic performance in male and female athletes engaged in Olympic combat sports. Using the PICOS framework, the study included original research on healthy, trained male and female athletes in Olympic combat sports. These studies compared HIIT interventions (lasting at least 4 weeks) with control groups, focusing on aerobic and anaerobic performance outcomes. Studies that measured other fitness parameters, had non-randomized designs, or involved mixed interventions were excluded. A database search was conducted on February 1, 2025, through PubMed, Scopus, and Web of Science. Study quality and risk of bias were assessed using the Physiotherapy Evidence Database (PEDro) scale, while the GRADE scale was used to assess the certainty of evidence. After screening, 20 studies were deemed eligible for inclusion in this review. The results showed a significant effect of HIIT over control groups for maximal oxygen uptake, with a moderate effect size (ES = 1.007, 95% CI 0.701 to 1.312, p < 0.001). A significant, but small, effect favoring HIIT was also found for peak power output (ES = 0.528, 95% CI 0.102 to 0.954, p = 0.015). Furthermore, the analysis of mean power output showed a moderate significant effect of HIIT over controls (ES = 0.871, 95% CI 0.392 to 1.350, p < 0.001). In conclusion, HIIT, whether performed through running or sport-specific techniques, appears to effectively enhance both aerobic and anaerobic performance in athletes participating in Olympic combat sports. These improvements could contribute to better overall performance, supporting the physical and physiological demands of these sports.